5.2.53 Problems 5201 to 5300

Table 5.273: Second order linear ODE

#

ODE

Mathematica

Maple

17697

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = g \left (t \right ) \]

17698

\[ {}y^{\prime \prime }+4 y = g \left (t \right ) \]

17699

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 2 t^{3} \]

17700

\[ {}t y^{\prime \prime }-\left (t +1\right ) y^{\prime }+y = t^{2} {\mathrm e}^{2 t} \]

17701

\[ {}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }-y = 2 \left (t -1\right )^{2} {\mathrm e}^{-t} \]

17702

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 3 x^{{3}/{2}} \sin \left (x \right ) \]

17703

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = g \left (x \right ) \]

17704

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = g \left (x \right ) \]

17705

\[ {}t^{2} y^{\prime \prime }-2 y = 3 t^{2}-1 \]

17706

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = \ln \left (x \right ) x^{2} \]

17707

\[ {}t^{2} y^{\prime \prime }-2 t y^{\prime }+2 y = 4 t^{2} \]

17708

\[ {}t^{2} y^{\prime \prime }+7 t y^{\prime }+5 y = t \]

17709

\[ {}y^{\prime \prime }+y = g \left (t \right ) \]

17710

\[ {}t y^{\prime \prime }-\left (t +1\right ) y^{\prime }-y = t^{2} {\mathrm e}^{2 t} \]

17711

\[ {}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }-y = 2 \left (t -1\right )^{2} {\mathrm e}^{-t} \]

17712

\[ {}y^{\prime \prime }+2 y^{\prime }-2 y = 0 \]

17713

\[ {}9 y^{\prime \prime }+12 y^{\prime }+4 y = 0 \]

17714

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

17715

\[ {}6 y^{\prime \prime }+5 y^{\prime }+y = 0 \]

17716

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = t^{2} {\mathrm e}^{t}+7 \]

17717

\[ {}y^{\prime \prime }-5 y^{\prime }-6 y = t^{2}+7 \]

17718

\[ {}y^{\prime \prime }+4 y = 3 \,{\mathrm e}^{-2 t} \sin \left (2 t \right ) \]

17719

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = t \cos \left (2 t \right ) \]

17722

\[ {}y^{\prime \prime }+16 y = \left \{\begin {array}{cc} 1 & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right . \]

17723

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} t & 0\le t <1 \\ 0 & 1\le t \end {array}\right . \]

17724

\[ {}y^{\prime \prime }+4 y = \left \{\begin {array}{cc} t & 0\le t <1 \\ 1 & 1\le t \end {array}\right . \]

17725

\[ {}y^{\prime \prime }-4 y^{\prime }-12 y = 0 \]

17726

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = t \]

17727

\[ {}y^{\prime \prime }-8 y^{\prime }+25 y = 0 \]

17728

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

17729

\[ {}y^{\prime \prime }-2 y^{\prime }+4 y = 0 \]

17730

\[ {}y^{\prime \prime }+4 y^{\prime }+29 y = {\mathrm e}^{-2 t} \sin \left (5 t \right ) \]

17731

\[ {}y^{\prime \prime }+w^{2} y = \cos \left (2 t \right ) \]

17732

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = \cos \left (t \right ) \]

17733

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = {\mathrm e}^{-t} \]

17734

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 18 \,{\mathrm e}^{-t} \]

17749

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} 1 & 0\le t <\frac {\pi }{2} \\ 0 & \frac {\pi }{2}\le t \end {array}\right . \]

17750

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \left \{\begin {array}{cc} 0 & 0\le t <\pi \\ 1 & \pi \le t \le 2 \pi \\ 0 & t \le 2 \pi \end {array}\right . \]

17751

\[ {}y^{\prime \prime }+4 y = \sin \left (t \right )-\operatorname {Heaviside}\left (t -2 \pi \right ) \sin \left (t \right ) \]

17752

\[ {}y^{\prime \prime }+4 y = \sin \left (t \right )-\operatorname {Heaviside}\left (t -\pi \right ) \sin \left (t \right ) \]

17753

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \left \{\begin {array}{cc} 1 & 0\le t <10 \\ 0 & 10\le t \end {array}\right . \]

17754

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \operatorname {Heaviside}\left (t -2\right ) \]

17755

\[ {}y^{\prime \prime }+y = \operatorname {Heaviside}\left (t -3 \pi \right ) \]

17756

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = t -\operatorname {Heaviside}\left (t -\frac {\pi }{2}\right ) \left (t -\frac {\pi }{2}\right ) \]

17757

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} \frac {t}{2} & 0\le t <6 \\ 3 & 6\le t \end {array}\right . \]

17758

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = \left \{\begin {array}{cc} \sin \left (t \right ) & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right . \]

17759

\[ {}y^{\prime \prime }+4 y = \operatorname {Heaviside}\left (t -\pi \right )-\operatorname {Heaviside}\left (t -3 \pi \right ) \]

17762

\[ {}u^{\prime \prime }+\frac {u^{\prime }}{4}+u = \frac {\left (\left \{\begin {array}{cc} 1 & \frac {3}{2}\le t <\frac {5}{2} \\ 0 & \operatorname {otherwise} \end {array}\right .\right )}{2} \]

17763

\[ {}u^{\prime \prime }+\frac {u^{\prime }}{4}+u = \left \{\begin {array}{cc} 1 & \frac {3}{2}\le t <\frac {5}{2} \\ 0 & \operatorname {otherwise} \end {array}\right . \]

17764

\[ {}u^{\prime \prime }+\frac {u^{\prime }}{4}+u = 2 \left (\left \{\begin {array}{cc} 1 & \frac {3}{2}\le t <\frac {5}{2} \\ 0 & \operatorname {otherwise} \end {array}\right .\right ) \]

17765

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \delta \left (t -\pi \right ) \]

17766

\[ {}y^{\prime \prime }+4 y = \delta \left (t -\pi \right )-\delta \left (t -2 \pi \right ) \]

17767

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \delta \left (t -\pi \right )+\operatorname {Heaviside}\left (t -10\right ) \]

17768

\[ {}y^{\prime \prime }-y = -20 \delta \left (t -3\right ) \]

17769

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = \sin \left (t \right )+\delta \left (t -3 \pi \right ) \]

17770

\[ {}y^{\prime \prime }+4 y = \delta \left (t -4 \pi \right ) \]

17771

\[ {}y^{\prime \prime }+y = \delta \left (t -2 \pi \right ) \cos \left (t \right ) \]

17772

\[ {}y^{\prime \prime }+4 y = 2 \delta \left (t -\frac {\pi }{4}\right ) \]

17773

\[ {}y^{\prime \prime }+y = \operatorname {Heaviside}\left (t -\frac {\pi }{2}\right )+3 \delta \left (t -\frac {3 \pi }{2}\right )-\operatorname {Heaviside}\left (t -2 \pi \right ) \]

17774

\[ {}2 y^{\prime \prime }+y^{\prime }+6 y = \delta \left (t -\frac {\pi }{6}\right ) \sin \left (t \right ) \]

17775

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \cos \left (t \right )+\delta \left (t -\frac {\pi }{2}\right ) \]

17777

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{2}+y = \delta \left (t -1\right ) \]

17778

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{4}+y = \delta \left (t -1\right ) \]

17779

\[ {}y^{\prime \prime }+y = \delta \left (t -1\right ) \]

17780

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{5}+y = k \delta \left (t -1\right ) \]

17781

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{10}+y = k \delta \left (t -1\right ) \]

17782

\[ {}y^{\prime \prime }+w^{2} y = g \left (t \right ) \]

17783

\[ {}y^{\prime \prime }+6 y^{\prime }+25 y = \sin \left (\alpha t \right ) \]

17784

\[ {}4 y^{\prime \prime }+4 y^{\prime }+17 y = g \left (t \right ) \]

17785

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 1-\operatorname {Heaviside}\left (t -\pi \right ) \]

17786

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = g \left (t \right ) \]

17787

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \cos \left (\alpha t \right ) \]

17790

\[ {}\frac {7 y^{\prime \prime }}{5}+y = \operatorname {Heaviside}\left (t \right ) \]

17791

\[ {}\frac {8 y^{\prime \prime }}{5}+y = \operatorname {Heaviside}\left (t \right ) \]

17893

\[ {}y^{\prime \prime } = \sin \left (x \right ) \]

17995

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+n \left (n +1\right ) y = 0 \]

17996

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}+y = 0 \]

17997

\[ {}y^{\prime \prime } \sin \left (x \right )^{2} = 2 y \]

18001

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 2 x^{3} \]

18002

\[ {}y^{\prime \prime }+\frac {x y^{\prime }}{1-x}-\frac {y}{1-x} = x -1 \]

18005

\[ {}y^{\prime \prime }+y = 0 \]

18006

\[ {}y^{\prime \prime }+\frac {y}{\ln \left (x \right ) x^{2}} = {\mathrm e}^{x} \left (\frac {2}{x}+\ln \left (x \right )\right ) \]

18007

\[ {}y^{\prime \prime }+p_{1} y^{\prime }+p_{2} y = 0 \]

18008

\[ {}\left (2 x +1\right ) y^{\prime \prime }+\left (4 x -2\right ) y^{\prime }-8 y = 0 \]

18009

\[ {}y^{\prime \prime } \sin \left (x \right )^{2}+\sin \left (x \right ) \cos \left (x \right ) y^{\prime } = y \]

18014

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

18016

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = x^{2} \]

18017

\[ {}y^{\prime \prime }-6 y^{\prime }+8 y = {\mathrm e}^{x}+{\mathrm e}^{2 x} \]

18020

\[ {}y^{\prime \prime }+4 y = \sin \left (2 x \right ) x \]

18021

\[ {}y^{\prime \prime }+y^{\prime }+y = {\mathrm e}^{-\frac {x}{2}} \sin \left (\frac {\sqrt {3}\, x}{2}\right ) \]

18022

\[ {}y^{\prime \prime }-y = \frac {{\mathrm e}^{x}-{\mathrm e}^{-x}}{{\mathrm e}^{x}+{\mathrm e}^{-x}} \]

18023

\[ {}y^{\prime \prime }-2 y = 4 x^{2} {\mathrm e}^{x^{2}} \]

18024

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \sin \left (2 x \right ) \]

18025

\[ {}y^{\prime \prime }+9 y = \ln \left (2 \sin \left (\frac {x}{2}\right )\right ) \]

18026

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}-\frac {n \left (n +1\right ) y}{x^{2}} = 0 \]

18027

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x \]

18028

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+2 y = x \ln \left (x \right ) \]

18029

\[ {}x^{2} y^{\prime \prime }-2 y = x^{2}+\frac {1}{x} \]

18031

\[ {}\left (1+x \right )^{2} y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 4 \cos \left (\ln \left (1+x \right )\right ) \]

18032

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}+\left (1-\frac {m^{2}}{x^{2}}\right ) y = 0 \]